Efektivitas Role Play, Penayangan VCD dan Modul dalam Meningkatkan Keterampilan Komunikasi Terapeutik Mahasiswa Stikes Jenderal Ahmad Yani Yogyakarta - Riduan Zaki, Sri Werdati, Fatwa Sari Tetra Dewi (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Previous research found that 75% of one’s life was used for communication. Communication gives the meaning of life. More than half of the surgery clients was not satisfied with the preserved information. Client needs effective communication and social contact which was useful to obtained information. There was a lack of communication between nursing staff and client. Nurses communication style was focused on their duty. Their conversation tend to be short and could not exploitate client’s believe and anxiety. There was a research inhealth behavior trough education especially in therapeutic communication.Objective: This research was aimed to measure the effectiveness of role play, video compact disc (VCD) playing and module in improving therapeutic communication skill of nursing student of STIKES Jenderal Ahmad Yani Yogyakarta.Method: This was a quasi experimental research that used non-equivalent control group design with pretest-posttest. The subject of the research was nursing student of STIKES Jenderal Ahmad Yani and Surya Global Yogyakarta. The intervention group was 42 students while control group was 51 students. The sample was taken with purposive sampling. The instrument being used was questionaire, check list of observation, (VCD), module and role play scenario with a case example. The data collection was conducted by having structured interview and observation. The data was analyzed with independent t-test to measure the difference on knowledge, attitude and skill with significance level of p = 0.05 and paired t test.Result: This research showed that there was a significant influence on the therapeutic communication education toward improvement on knowledge with t = 9.463 and p = 0.000 (p < 0,05), attitude with t = 5.338 and p = 0.000 (p < 0.05), skill after education with t = 9.675 and p = 0.000 (p < 0.05), and skill after one month with t = 5.661 and p = 0.000 (p < 0.05). However, there was no significant difference on the skill after education and there was no significant difference after one month with t = -2.005 and p = 0.052 (p > 0.05).Conclusion: Role play, VCD playing and module were effective in improving knowledge, attitude and skill on therapeutic communication after given education and improving skill after 1 month and yet there was a decreasing on the average of skill value after 1 month compared with after given education.Keywords: therapeutic communication, knowledge, attitude, skill, role play, video compact disc, module